Respuesta :
Answer:
Answer:
f(x) = 5 + 2x
y+4x^2-1 is the same as y=-4x^2+1, then replace y with f(x); f(x)=-4x^2+1. After you do that, replace x with 2; f(2)=-4(2)^2+1. 2^2=4, 4 times -4=-16, -16+1=-15. So f(2)=-15.
Answer:
f(x) = 5 + 2x
Step-by-step explanation:
2y - 4x = 10
+4x +4x
2y = 10 + 4x
Now we have a new equation but we have to isolate the variable y.
[tex]\frac{2y}{2}[/tex] = [tex]\frac{10 + 4x}{2}[/tex] Then divide to solve for y.
y = 5 + 2x
Since f(x) is the same thing/equal to y we can just replace that.
f(x) = 5 + 2x
Hope that helps and have a great day!